Is there a Place for Bevacizumab in Patients with Extensive-Stage Small Cell Lung Cancer? - Roviello, Giandomenico; Generali, Daniele (Current Cancer Drug Targets, 2016)
It was estimated that small cell lung cancer (SCLC) accounts for about one Sixth of all lung cancer cases. Patients with SCLC are usually diagnosed in advanced stage of disease. Unfortunately at this stage, prognosis is very poor. Bevacizumab is a monoclonal antibody against VEGF, which inhibits the angiogenesis in malignant tumors. Although Bevacizumab has been approved for firstline use in advanced non-SCLC, the first report has been available for its use in SCLC. In this review, we summarized all available data on the use of Bev in SCLC patients. Finally, future directions are discussed.
Keywords: small cell